2021
DOI: 10.21037/atm-2020-ioi-07
|View full text |Cite
|
Sign up to set email alerts
|

The current state of navigation in robotic spine surgery

Abstract: The advent and widespread adoption of pedicle screw instrumentation prompted the need for image guidance in spine surgery to improve accuracy and safety. Although the conventional method, fluoroscopy, is readily available and inexpensive, concerns regarding radiation exposure and the drive to provide better visual guidance spurred the development of computer-assisted navigation.Contemporaneously, a non-navigated robotic guidance platform was also introduced as a competing modality for pedicle screw placement. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 58 publications
0
43
0
Order By: Relevance
“…The advantage of Chinese TIROBOT is that real-time navigation can be obtained according to the three-dimensional images during the operation. [ 29 ] However, some scholars have pointed out that in the process of 3D image reconstruction and registration, distortion will occur due to electromagnetic field deflection, which will affect the system error of the robot. [ 30 ] The accuracy of pedicle screw placement assisted by robot is more than 90%.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of Chinese TIROBOT is that real-time navigation can be obtained according to the three-dimensional images during the operation. [ 29 ] However, some scholars have pointed out that in the process of 3D image reconstruction and registration, distortion will occur due to electromagnetic field deflection, which will affect the system error of the robot. [ 30 ] The accuracy of pedicle screw placement assisted by robot is more than 90%.…”
Section: Discussionmentioning
confidence: 99%
“…An extensive number of peer reviewed journal publications have documented the use, efficacy safety and technical accuracy achieved with robotic-assisted spinal surgery. 23 , 28 , 30 , 37 , 39 - 41 , 44 - 46 , 93 - 123 The focus in reviewing these publications was to highlight the technical accuracy observations and determine a basis for discrepancy between planned versus actual final implant position based on postoperative CT images. In case studies where quantitative measurements were not reported, the Gertzbein and Robbins 124 score (GRS) was adopted to calculate pedicle screw implant position.…”
Section: Resultsmentioning
confidence: 99%
“…The upgrade included a fully integrated navigation interface and Zimmer Biomet instrumentation package as well as adaptation across cranial, spinal, and orthopedic knee arthroplasty procedures. 6…”
Section: The History Of Robotics In Spine Surgerymentioning
confidence: 99%
“…6,17,18 The TiRobot (Figure 7) 6,19,20 and the Asenus systems have not yet received FDA clearance for use in spine surgical procedures in the United States. 6…”
Section: The History Of Robotics In Spine Surgerymentioning
confidence: 99%
See 1 more Smart Citation